Zamia multidentata (Cycadales, Zamiaceae), a new arborescent species of Zamia from Acre, Brazil - Segalla, Rosane; Pimenta, Ricardo Soares; Calonje, Michael (Phytotaxa, 2023)
Zamia multidentata is described and illustrated here as a new species from the Amazon basin, state of Acre, Brazil. The new species shares morphological similarities with the Amazonian species Z. hymenophyllidia, and Z. urep, to which it is compared. The combination of slender (to 6.2 cm) caulescent stems, strongly serrulate elliptic leaflets with long acuminate tips and a pronounced adaxially raised longitudinal crease, as well as seed strobili with long peduncles (15 cm +) and flat megasporophylls distinguish the new species Zamia multidentata from all other known species in the genus.